Individual, household, and community level risk factors of stunting in children younger than 5 years: Findings from a national surveillance system in Nepal. Issue 1 (23rd February 2017) - Dorsey, Jamie L.; Manohar, Swetha; Neupane, Sumanta; Shrestha, Binod; Klemm, Rolf D. W.; West, Keith P.
Abstract: Despite substantial reductions in recent years in Nepal, stunting prevalence in children younger than 5 years remains high and represents a leading public health concern. To identify factors contributing to the stunting burden, we report multilevel risk factors associated with stunting in 4, 853 children aged 6–59 months in a nationally and agroecologically representative random sample from the first year of the Policy and Science for Health, Agriculture, and Nutrition Community Studies, a community‐based observational, mixed‐panel study. Mixed effects logistic regressions controlling for multilevel clustering in the study design were used to examine the association of individual‐, household‐, and community‐level factors associated with stunting. Stunting prevalence was 38% in our sample. After adjustment for potential confounding variables, maternal factors, including maternal height and education, were generally the strongest individual‐level risk factors for stunting, adjusted odds ratio (AOR) = 2.52, 95% CI [1.96, 3.25], short (<145 cm) versus not short mothers; AOR = 2.09, 95% CI [1.48, 2.96], uneducated mothers versus secondary school graduates. Among the household‐ and community‐level factors, household expenditure and community infrastructure (presence of paved roads, markets, or hospitals) were strongly, inversely associated with increased stunting risk, AOR = 1.68, 95% CI [1.27, 2.24], lowest versus highest household expenditure quintile; AOR = 2.38, 95% CI [1.36, 4.14], less developed (lacking paved roads, markets, or hospitals) versus more developed communities. Although most factors associated with stunting are not rapidly modifiable, areas for future research and possible interventions emerged.